Correlates, causes, and consequences of fat talk: A review. (September 2015) - Shannon, Amy; Mills, Jennifer S.
Highlights: Narrative synthesis is used to integrate fat talk research from 1994 to 2014. Fat talk is prevalent and has been linked with a number of maladaptive outcomes. Evidence suggests anxiety reduction and social cohesion motivate fat talk. Empirically supported interventions for fat talk would be a worthwhile endeavour. Abstract: Fat talk is a term used to describe self-disparaging remarks made to other people about one's weight or body. Fat talk has been both causally and correlationally linked to a number of negative body image-related variables including low body esteem, body dissatisfaction, drive for thinness, body-related cognitive distortions, and perceived sociocultural pressure to be thin. As such, body image researchers and clinicians would benefit from increased awareness of the current literature concerning fat talk. A narrative synthesis approach is used to summarize all research containing the keywords fat talk, body talk, or weight talk that was published from 1994 to 2014 inclusive. The measures used to study fat talk, outcomes and correlates associated with fat talk, theories that may help explain these findings, and the purpose served by fat talk are reviewed and discussed. In addition, directions for future research on fat talk, including intervention strategies, are examined.